2001
DOI: 10.1176/appi.ps.52.4.493
|View full text |Cite
|
Sign up to set email alerts
|

Consumer-Run Service Participation, Recovery of Social Functioning, and the Mediating Role of Psychological Factors

Abstract: The findings support the view that psychosocial factors may play a role in facilitating good community adjustment for individuals diagnosed as having serious mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 37 publications
2
65
1
Order By: Relevance
“…Other personal system variables, such as a more problem-focused coping style and more general self-efficacy, have also been found to predict better social functioning and life satisfaction in cross-sectional studies (Bechdolf et al, 2003;Eklund et al, 2003;Ritsner, BenAvi et al, 2003;Ritsner et al, 2000;Yanos, Primavera, & Knight, 2001). Two prospective studies support these findings.…”
Section: Enduring Environmental Conditions and Copingmentioning
confidence: 85%
See 2 more Smart Citations
“…Other personal system variables, such as a more problem-focused coping style and more general self-efficacy, have also been found to predict better social functioning and life satisfaction in cross-sectional studies (Bechdolf et al, 2003;Eklund et al, 2003;Ritsner, BenAvi et al, 2003;Ritsner et al, 2000;Yanos, Primavera, & Knight, 2001). Two prospective studies support these findings.…”
Section: Enduring Environmental Conditions and Copingmentioning
confidence: 85%
“…Evidence from cross-sectional research supports the view that the use of active, problemoriented coping strategies is related to better social functioning (Andres, Pfammatter, Fries, & Brenner, 2003;Lee, Lieh-Mak, Yu, & Spinks, 1993;Yanos et al, 2003;Yanos, Primavera et al, 2001). A longitudinal study (Boschi et al, 2000) found that individuals who reported that problem-centered coping strategies were most helpful to them at baseline had moderately better social functioning at 24 month follow-up than individuals who reported another type of strategy as most helpful.…”
Section: Coping and Functioning/well-beingmentioning
confidence: 91%
See 1 more Smart Citation
“…Overall, these studies suggested that self-help and peer support programs can promote empowerment and recovery [14][15]. Combined with a similar review by Solomon [5], preliminary evidence suggests that these programs decrease the need for acute mental health services and mental health hospitalizations [14,[16][17]; increase social support, functioning, and activities [16,[18][19]; decrease substance abuse [14,16]; and may benefit perceived quality of life [20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the potential benefits of consumer involvement in the planning and provision of services also merit further study. Mutual-support groups can facilitate the process of recovery by helping individuals view themselves and their problems as less deviant and alter understanding of self (DenBoer, Wiersma, & Van Den Bosch, 2004;Rummel, Hansen, & Helbig, 2005;Yanos, Primavera, & Knight, 2001;Young, Green, & Estroff, 2008). Public policies can also impact motivation and willingness to participate in recovery-oriented programs, such as supported employment services.…”
Section: Related Concerns That Affect Recoverymentioning
confidence: 99%